The Influence of Perception of Ease and Perception of Trust on Intention to Reuse E-Wallet Dana in Surabaya - I Putu Widhi Prabawa; Siti Aminah (Jurnal Ekonomi dan Bisnis Digital, 2023)
The purpose of this study is to explain the influence of convenience perception and trust perception on reuse interest with fund e-wallet research objects in Surabaya. This study used a quantitative approach. The population in this study is Surabaya residents who have shopped and transacted using e-wallet funds. While the sample in this study is students using e-wallet funds in Surabaya. The method used to collect non-probability sampling samples with purposive sampling techniques with a total of 96 respondents. Tests using the SmartPLS application show that all tests get values above the values that have been required for the test to be declared reliable. This study used quantitative research design, data analysis in the form of descriptive statistics and PLS analysis. The results showed that the perception of convenience had a positive and significant effect on interest in reuse. Then on the perception of trust has a positive and significant effect on interest in reuse.